Day 2 Thu, September 06, 2018 2018
DOI: 10.2118/191770-ms
|View full text |Cite
|
Sign up to set email alerts
|

Production Induced Stress Change Impact on Infill Well Flowback Operations in Permian Basin

Abstract: As many unconventional basins are maturing, infill well drilling and completion has taken the center stage in the development phase. Most operators now realize the importance of incorporating the geomechanical changes induced by stimulation and production of the parent wells while placing infill child wells. But after drilling and completion, post-stimulation flowback is also critical in maintaining well productivity and performance. To optimize field management strategy, a comprehensive understanding of the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…They also determine the direction of the fracture propagation and well postfracturing production. Practical experiences in the Permian Basin of the United States have shown that the production of the parent wells can alter the magnitude and the azimuthal orientation of the in-situ stresses, thereby influencing the production of the infill wells (Pankaj, 2018;Zheng et al, 2018). Considering the inter-well stress evolution pattern in Marcellus shale, the optimal well spacing was determined by establishing the relationship between well spacing and single well fracturing scale (Jaripatke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They also determine the direction of the fracture propagation and well postfracturing production. Practical experiences in the Permian Basin of the United States have shown that the production of the parent wells can alter the magnitude and the azimuthal orientation of the in-situ stresses, thereby influencing the production of the infill wells (Pankaj, 2018;Zheng et al, 2018). Considering the inter-well stress evolution pattern in Marcellus shale, the optimal well spacing was determined by establishing the relationship between well spacing and single well fracturing scale (Jaripatke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Shale is essentially heterogeneous, which develops a large number of bedding planes (BPs) and natural fractures (NFs). Therefore, the propagation path of HFs is not only affected by the stress field but also related to the distribution characteristics of BPs and NFs . HFs separate part of net pressure to open NFs in the process of propagation, so the HFs may deflect along the direction of NFs.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the propagation path of HFs is not only affected by the stress field but also related to the distribution characteristics of BPs and NFs. 24 HFs separate part of net pressure to open NFs in the process of propagation, so the HFs may deflect along the direction of NFs. In addition, the propagation direction of HFs will also be deflected due to the significant difference in the stress field and rock physical properties on the upper and lower sides of the BPs.…”
Section: Introductionmentioning
confidence: 99%